Answer:
x = -19/3 y = 10 write as an ordered pair (-19/3, -10)
Explanation:
Step 1: 'Elimination' is done through adding or subtracting. You want to add the two equations together to get rid of one of the variables.
Since the x values have coefficients with opposite signs (-9 and 9), add the two functions together. The result is...
-2y = 20 { -9x + 9x = 0, so x is gone, 4y + (-6y) = -2y, 17 + 3 = 20 }
Step 2: Now solve for the remaining variable, in this case, 'y'
-2y = 20 (divide both sides by -2 to isolate the variable)
y = -10
Step 3: Plug the value for 'y' into one of the original equations to find 'x'
-9x + 4(-10) = 17 ('y' becomes -10)
-9x - 40 = 17 { 4(-10) = -40 } (now add 40 to both sides)
-9x = 57 (divide both sides by -9 to isolate 'x' )
x = -57/9 (now reduce, both are multiples of 3, so divide 3 out)
x = -19/3 ( -57/3 = -19, 9/3 = 3 )